Phytochemical and biological potential of Prickly pear (Opuntia ficus-indica) extracts from M’sila (Algeria) - Hamidi, Bendif (Algerian Journal of Biosciences, 2023)
The cladodes juice and seeds oil obtained from the prickly pear (Opuntia ficus-indca) grown in M’sila, Algeria are investigated in this work. The objective of the present study was to evaluate their physicochemical composition, polyphenols and flavonoid content, antioxidant potential by DPPH test and antibacterial activities. The results of this experimental study showed that leaf bud juice presented the highest yield of 79.02%. Leaf juice was rich in polyphenols (4.6 g/100 g) and flavonoids (38.35 mg/100 g). While, the study revealed that the seeds oil extracts presented a weak yield of 5%. Leafy sap from spiny species shows high antioxidant activity and an antibacterial effect on: S. aurous, E. coli, S. typhimirum, S. marcesscens. Whereas, the antibacterial activities were as follows: for leafy sap from spiny species E. coli, P. aeruginosa, S. typhimirum and K. pneumoniae strains were relatively resistant to oil, E. coli and S. marcescens strains were relatively resistant to cold-pressed oil. The three oil varieties cold, 90°, and 160° pressed oil, were the most proven oils to be effective against E. coli, P. aeruginosa, S. typhimirum and K. pneumonia.